A new way to think : your guide to superior management effectiveness - Martin, Roger L. (Boston, Massachusetts : Harvard Business Review Press, 2022)
"If you could imagine the ultimate guide to the essentials of strategy and management, from one of the world's top business thinkers, what would that look like? It would look like this book. Over a stellar career, Roger Martin has advised CEOs of some of the world's most successful companies. From the beginning, he noted that almost every executive he talked to had a "model"-a framework or way of thinking that guided their strategy and activities. But these models tended to become automatic, so much so that when one didn't work, the response was typically to just apply it again-with greater enthusiasm. Martin took a fresh, critical approach to helping. When company leaders came to him with fundamental questions-How do you decide where to play and how to win? What is the key to shaping and changing corporate culture? How can you design a successful, sustainable innovation process? -his first response was to break the spell of the current model with a memo articulating a new way to think about the problem at hand, and a more powerful and effective way to successfully overcome it. Over time, these ideas worked their way into Martin's many Harvard Business Review articles. Now, for the first time, they appear together in A New Way to Think. With his trademark incisive intellect and clarity, Martin covers the entire breadth of the management landscape-illuminating the true nature of competition, explaining how company success revolves around customers, revealing how strategy and execution are really the same thing, and much more. Reading like a series of one-on-one sessions with one of the world's leading business thinkers, A New Way to Think is an essential primer for any current or aspiring business leader"--
Introduction : Thinking differently about the essentials of management -- Part one: On context. Competition -- Stakeholders -- Customers -- Part two: Making choices. Strategy -- Data -- Part three: Structuring work. Culture -- Knowledge work -- Corporate functions -- Part four: Key activities. Planning -- Execution -- Talent -- Innovation -- Capital investment -- M&A -- Afterword.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (ProQuest Ebook Central, viewed April 11, 2023).
WorldCat record variable field(s) change: 050
Keywords: Creative ability in business; Success in business; Industrial management; Organizational effectiveness; Créativité dans les affaires; Succès dans les affaires; Gestion d'entreprise.; Efficacité organisationnelle; Creative ability in business; Industrial management; Organizational effectiveness; Success in business